Digital prosthodontics in near future: Awareness among the dental students on intraoral scanners and its probability of replacement over conventional method in the near future of prosthodontics: A cross-sectional survey - N. Ketharinath; T. Kiruppashini; P. Kabilan; C. Nagappan (Wolters Kluwer Medknow Publications, 2024)
Aims: The aim of the study is to analyse the awareness and knowledge about IOSs among the dental students of Tamil Nadu. Settings and Design: A cross sectional survey - questionnaire study. Materials and Methods: A descriptive, cross-sectional survey was carried out to assess the knowledge, awareness, and practice of IOSs among dental students through a questionnaire of five domains, with five questions in each domain. This is sent to various dental students of Tamil Nadu through mail and othersocial media platforms. Statistical Analysis Used: It was performed using a statistical package for the social sciences' [SPSS] software version 22. Descriptive statistics were performed for demographic variables. Chi square test was performed for all the qualitative data. Results: Most of the answers were statistically significant with P < 0.05 and few results were not significant indicating less knowledge and awareness about digital prosthodontics among the dental students. Conclusions: Thus, the addition of digital dentistry in the curriculum of dental students and giving them more knowledge helps in the flourishment of the future prosthodontic field with much accuracy of treatment and with less patient discomfort replacing the conventional methods.